Desain Konseptual Berbasis Research And Development Model 4D Dalam Pengembangan Kurikulum PAI Adaptif Bagi Peserta Didik Dengan Disabilitas Intelektual - Barkatullah Amin; Nuril Huda; Dina Hermina; Aulia Azmina Fajriati (Universitas Garut, 2025)
This paper formulates a conceptual design of an adaptive Islamic Education (PAI) curriculum for students with intellectual disabilities (PDDI) using an illustrative application of the 4D R&D Model developed by Thiagarajan, Semmel, and Semmel. As a literature-based study, it employs the Define, Design, Develop, and Disseminate stages to map the curriculum development process without empirical testing. The Define stage identifies PDDI needs through a synthesis of literature on special education and PAI curriculum. The Design stage presents a hypothetical framework emphasizing multisensory media, concrete strategies, and realistic learning goals. The Develop stage provides theoretical validation through expert judgment. The Disseminate stage highlights institutional and policy support required for implementation. The result is a conceptual adaptive PAI curriculum model that may guide future empirical studies and policy development for PDDI in both special and inclusive schools.